HUBUNGAN MODEL PEMBELAJARAN KONTEKSTUAL DENGAN IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI - Siti Zayyana Ulfah; Udin Syaefudin Sa’ud; Atep Sujana; Sahroni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to explore the integration of contextual and differentiated learning models in creating a learning environment that suits the needs of students at different levels of education. Based on the theory of constructivism, contextual learning encourages students to relate material to real-life experiences, while differentiated learning customizes content, processes and products based on students' individual needs. The research method uses a literature study approach to explore strategies to improve teachers' understanding, such as professional training, collaboration and integration of educational technology. The results show that the combination of these two models can improve concept understanding, critical thinking skills and student motivation. The study also highlights the importance of teacher engagement in creating learning experiences that are relevant and responsive to student diversity. Combining contextual and differentiated learning can support the improvement of education quality by meeting the needs of diverse students.